THE ROLE OF THE DEPARTMENT FOR INCREASING THE SOCIAL AND POLITICAL ACTIVITY OF WOMEN AND GIRLS WORKING IN POLITICAL PARTIES IN UZBEKISTAN IN THE SOCIAL AND POLITICAL LIFE OF THE COUNTRY (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article analyzes the role of the Women's Socio-Political Activity Department in the social and political life of the country, the increasing participation of women in elections, their share in parliament and state administration, the role of political parties in increasing the social and political activity of women, ensuring and protecting their rights and interests, and the principles of building a welfare state.
Keywords: Political activism, electoral system, political parties, women, local councils, Senate, Oliy Majlis, welfare state, gender equality, Political Council.